Biotargets of cancer in current clinical practice - Bologna, Mauro (Current Clinical Pathology, 2012)
Biotargets of Cancer in Current Clinical Practice presents an updated and reasoned review of the current status of knowledge concerning the major cancer types with a special focus on the current biomarkers, genes involved and the potential future targets of innovative therapies. The volume includes for each major cancer type, a comprehensive although concise discussion of epidemiology, affirmed and innovative biomarkers for diagnosis, and descriptions of the relevant genes for prognosis and (individualized) therapy through biotarget-specific new molecular treatments, with the latest information on the validation status of each novel biomarker. Individual chapters are dedicated to the major cancer types, plus a special chapter on metastasis. The present debate on patentability of genetic information applied to diagnostics and therapeutics of cancer is also discussed.